2017
DOI: 10.21699/jns.v6i2.559
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal Malformations: Histomorphological and Immunohistochemical Evaluation of Neuronal Dysfunction

Abstract: Objective :The patients with anorectal malformations (ARM) have been identified with specific and non-specific pathological changes. The present study was conducted with the aim to study histomorphological changes and various immunohistochemical (IHC) markers (calretinin, S-100, CD117) in intestinal wall specimens to assess neuronal dysfunction in ARM patients.Material and methods :Thirty children having ARM were included in our study. In all the cases, a representative biopsy was received. The tissue sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…However, the brosis of the rectal pouch in ARM is also common and easily overlooked. The subepithelial brosis was found in 71% of the cases from the research of Pandey et al and in 90% from Gangopadhyay et al [9,29]. In accordance with the report form Lombardi et al, our previous research also found the brosis of muscularis propria of the distal rectum from 52 patients with ARM [7,8,10].…”
Section: Discussionsupporting
confidence: 87%
“…However, the brosis of the rectal pouch in ARM is also common and easily overlooked. The subepithelial brosis was found in 71% of the cases from the research of Pandey et al and in 90% from Gangopadhyay et al [9,29]. In accordance with the report form Lombardi et al, our previous research also found the brosis of muscularis propria of the distal rectum from 52 patients with ARM [7,8,10].…”
Section: Discussionsupporting
confidence: 87%
“…Bhatia et al [ 26 ] reported that the distal rectal pouch in ARM show various specific and nonspecific histomorphologic changes, and the postoperative dysmotility can be attributed to the significantly alteration in density and distribution of ICCs. In addition, several studies also reported that the density and distribution of ganglia gradually decreased distally along the rectum, consistent with reports by others.…”
Section: Discussionmentioning
confidence: 99%
“…Our clinical results indicated that megarectum might be an important cause of postoperative constipation in patients with congenital rectovestibular fistula or perineal fistula. Bhatia et al ( 17 ) reported that the rectal Cajal interstitial cells and ganglion cells were reduced in children with AMR, and the content of calretinin was also reduced ( Figure 2 ). Mandhan et al ( 18 ) found that the decreased expression of neuron-specific enolase, vasoactive intestinal peptide and substance P in the rectum of AMR fetal rats may lead to rectal motility disturbance and become the pathological basis of constipation.…”
Section: Discussionmentioning
confidence: 95%